An Examination of Investment Potential in Georgia’s Hotel Industry: The Role of EVA and Tourism - Tamar Gamsakhurdia; Lamara Kadagidze; Salome Ioseliani (European Scientific Journal, ESJ, 2025)
The tourism sector plays a significant role in the economic advancement of both developing and developed countries. The present study examines the economic potential and investment opportunities in Georgia's hotel industry, utilizing the Economic Value Added (EVA) coefficient as the primary indicator. The objective of the research was to evaluate the EVA coefficient for hotels across various regions of Georgia and to analyze its impact on the number of foreign tourists and hotel revenues. A mixed-methods approach was employed in the study, incorporating both quantitative and qualitative analyses. The dynamics of financial data were examined, and regression analysis was applied to calculate the EVA coefficient and to determine the relationship between the growth of tourist flows and financial performance metrics. The key findings indicated that Georgia’s hotel sector was attractive to investors and contributed significantly to economic growth. The results demonstrated an increase in the EVA coefficient and its positive impact on economic sustainability, as well as a correlation between the growth of tourist flows and financial success. The research also provides recommendations that include enhancing transparency in financial data, improving the accessibility of information for investors, and adopting technological innovations to strengthen the sustainability of the tourism sector and foster economic development.